Research on the characterization of surface load on concrete column subjected to blast loads - Wang, Z.; Zhang, B.; Hao, Hong; Li, J.; Bai, C. (2012)
The determination of the load on the surface of structural element subjected to the blast loading is one of the most important issues in the anti-blast design. For the common column, the influence of deflection effect of shock wave around the column on the load characteristic is magnificent as the section of column is small compared with its length. It is meaningful to establish the characteristic of the load distribution on the column surface. The distribution of load on the column was studied through the field test and the numerical simulation. Through the test the real loads and their variation history were measured. Based on the test, a series of numerical simulations were done to analyze the loads on the columns with different sizes of the section. The relation between loads and the column sizes were established. The calculated results were in agreement with the measured results. These results are useful to the anti-blast design of construction.